Aproveitamento de resíduos industriais de goiaba (Psidium guajava L.) para a elaboração de pré-misturas para bolos - Ferreira, Maria Izabel Carneiro (2023)
The guava agroindustry produces residues, such as peels and seeds, in considerable quantities, which can serve as alternative sources of nutrients for human nutrition. In this context, this study aimed to characterize the flour made from guava peels in terms of its physicochemical and technological properties, to be used in new food products. Physicochemical, phytochemical, and technological analyses were carried out to characterize the flour from guava peels, which presented a moisture content of 7.63%, 3.94% ash, 5.59% lipids, 1.61% proteins, 7.30% soluble dietary fiber, 40.52% insoluble dietary fiber, 47.82% total fibers, 88.86% carbohydrates, pH 3.86, total titratable acidity of 4.74%, and 183.25 mg/100g of ascorbic acid. We found 1.80 μg/mL chlorophyll a, 1.74 μg/mL of chlorophyll b, and 739.34 μg/mL of total carotenoids as bioactive compounds. The phytochemical screening of this flour showed negative results for alkaloids, amide, anthraquinones, anthocyanins, and flavonoids. And moderately positive results for coumarins, digitalis heterosides, especially strongly positive results, for reducing sugars, steroids and triterpenes, saponins, and tannins. The reducing sugars, steroids and triterpenes, saponins, and tannins showed strongly positive qualitative results in the FCG. Regarding the technological properties of guava peel flour, the water solubility index was observed to be 7.57 g/100 g, water absorption capacity (g/g) of 4.50, oil absorption capacity (g/g) of 1.45, apparent density (g/mL) of 0.43, hygroscopicity of 5.05, and water activity of 0.34. As for the color of the flour, L* of 72.27 was observed, which is closer to the dark region, a* equal to 4.80, and for the b* component 29.82, indicating low intensity to red and close to yellow, consistent with the visual coloration of the fruits. The cakes made containing guava peel flour presented high dietary fiber contents. The use of food industry residues such as guava peels and their incorporation in the form of guava peel flour, can be an alternative for application and value addition in different food products, due to their physicochemical properties and good technological quality of their flour. In addition to contributing to the reduction of organic waste accumulation from the agroindustry, representing an innovation in the food industry. It is suggested that further studies related to guava peel flour be carried out, as it presents nutritional potential in relation to its bioactive components.